Bimbingan Belajar Gratis Mata Pelajaran Matematika Tingkat SD di Yayasan Kencana Bakti Semesta (YKBS) Badung Bali - Rahmawati, Suci; Chonnaniyah, Chonnaniyah; Lestari, Windy (LPPM Universitas Timor, 2023)
Parents' hope for their children pursuing formal education is to get maximum test scores and graduate with good grades. Thus, some efforts are made by parents to increase children's understanding of learning. Non-formal education at tutoring institutions is one of the parents' efforts. However, not all parents can provide tutoring facilities through non-formal institutions. Concrete steps are needed from various elements of society to overcome these problems, one of which is a lecturer. Lecturers carry out community service (PKM) by giving free mathematics tutoring at the elementary level within the Badung Bali Kencana Bakti Semesta Foundation (YKBS). The PKM aims to develop good learning habits, increase learning motivation, and increase learning achievement in mathematics. Tutoring is carried out 14 times, held on Wednesdays and Saturdays. The material provided refers to the students' textbooks and worksheets. A series of activity methods, namely (1) warming up through giving motivation to learn (2) explaining the material, (3) questions and answers, (4) quiz, (5) giving gifts, (6) giving post-test. The PKM activity can improve students' learning outcomes, as shown by the post-test results. The development of student motivation also shows good results, shown by the enthusiasm of students who ask for continuous tutoring activities.